PARANOIA IN THOMAS PYNCHON'S “THE CRYING OF LOT 49” - Oktaviani, Naila Dwinanda; Haurani, Najwa Djafira; Utami, Regita Permata; Nurholis, Nurholis (Cahaya Ilmu Bangsa Institute, 2025)
This paper explores the enduring theme of Paranoia in Thomas Pynchon’s novel “The Crying of Lot 49,” with a particular emphasis on the protagonist, Oedipa Maas. In the story, Paranoia arises as a reaction to the intricate and uncertain nature of the modern world portrayed by Pynchon. Through symbols such as the muted post horn and Tristero’s conspiratorial network, Oedipa is caught up in a never-ending search for meaning. As Oedipa delves deeper into her investigation, she experiences a mental crisis characterized by paranoia and disorientation. The more Oedipa gathers information about Tristero, the higher her paranoid levels become. She feels that everything she sees, smells, dreams and remembers will be interwoven into Tristero. This creates a tension between what is real and what is imagined. She wonders if all these clues really exist or are just imaginary. This creates a strong internal debate, making it difficult for her to believe in anything. With this discussion of paranoia in the novel, we as readers can explore how paranoia not only affects Oedipa’s perception of the world around her, but also illustrates Pynchon’s critique of social and political structures that oppress individuals.